Inhibitory member of the apoptosis-stimulating protein of p53 is overexpressed in bladder cancer and correlated to its progression. Issue 19 (May 2017) - Wu, Ziyu; Wang, Sugui; Xue, Peng; Wang, Shoulin; Wang, Gongcheng; Zhang, Wei
Abstract : Abstract: Several lines of direct evidence show that inhibitory member of the apoptosis-stimulating protein of p53 (iASPP) has an important function in cancer progression. However, its expression pattern and relationship with clinical pathologic characteristics in bladder cancer (BC) have not been completely elucidated. In this study, firstly, samples from 3 patients with invasive BC were detected by liquid chromatography tandem mass spectrometry to confirm overexpression of iASPP in BC, then samples from patients with noninvasive and invasive BC were detected by real-time polymerase chain reaction, Western blot, and tissue microarry immunohistochemistry. The relationship between iASPP expression and various clinicopathological features was investigated. The results showed m-RNA and protein of iASPP were overexpressed in BC and the rate of iASPP-positive cells was positively correlated with Union for International Cancer Control-Tumor, Node, Metastases stage, histologic grade, lymph node metastasis and poor overall survive. The data demonstrate that iASPP is overexpressed in BC and promotes the malignancy of BC. iASPP maybe serve as a potential therapeutic target for BC. Abstract : Supplemental Digital Content is available in the text